Modeling Na+-Ca2 + exchange in the heart: Allosteric activation, spatial localization, sparks and excitation-contraction coupling. (October 2016) - Chu, Lulu; Greenstein, Joseph L.; Winslow, Raimond L.
Abstract: The cardiac sodium (Na + )/calcium (Ca 2 + ) exchanger (NCX1) is an electrogenic membrane transporter that regulates Ca 2 + homeostasis in cardiomyocytes, serving mainly to extrude Ca 2 + during diastole. The direction of Ca 2 + transport reverses at membrane potentials near that of the action potential plateau, generating an influx of Ca 2 + into the cell. Therefore, there has been great interest in the possible roles of NCX1 in cardiac Ca 2 + -induced Ca 2 + release (CICR). Interest has been reinvigorated by a recent super-resolution optical imaging study suggesting that ~ 18% of NCX1 co-localize with ryanodine receptor (RyR2) clusters, and ~ 30% of additional NCX1 are localized to within ~ 120 nm of the nearest RyR2. NCX1 may therefore occupy a privileged position in which to modulate CICR. To examine this question, we have developed a mechanistic biophysically-detailed model of NCX1 that describes both NCX1 transport kinetics and Ca 2 + -dependent allosteric regulation. This NCX1 model was incorporated into a previously developed super-resolution model of the Ca 2 + spark as well as a computational model of the cardiac ventricular myocyte that includes a detailed description of CICR with stochastic gating of L-type Ca 2 + channels and RyR2s, and that accounts for local Ca 2 + gradients near the dyad via inclusion of a peri-dyadic (PD) compartment. Both models predict that increasing the fraction of NCX1 in the dyad and PD decreases spark frequency, fidelity, and diastolic Ca 2 + levels. Spark amplitude and duration are less sensitive to NCX1 spatial redistribution. On the other hand, NCX1 plays an important role in promoting Ca 2 + entry into the dyad, and hence contributing to the trigger for RyR2 release at depolarized membrane potentials and in the presence of elevated local Na + concentration. Whole-cell simulation of NCX1 tail currents are consistent with the finding that a relatively high fraction of NCX1 (~ 45%) resides in the dyadic and PD spaces, with a dyad-to-PD ratio of roughly 1:2. Allosteric Ca 2 + activation of NCX1 helps to "functionally localize" exchanger activity to the dyad and PD by reducing exchanger activity in the cytosol thereby protecting the cell from excessive loss of Ca 2 + during diastole. Highlights: A novel mechanistic model is formulated for dynamic Ca 2 + -dependent allosteric regulation of NCX1. The NCX1 model is incorporated into both a super-resolution model of Ca 2 + spark generation and a stochastic ventricular myocyte model. Results in both models predict that Ca 2 + spark frequency decreases with increasing dyad and/or peri-dyad NCX1 localization. Whole-cell modeling results are quantitatively consistent with recent imaging data indicating t-tubule NCX1 localization levels. NCX1 promotes Ca 2 + entry across the sarcolemma into the dyad at depolarized Vm and in the presence of elevated local [Na + ].